Joel Martins: o tempo vivido entre o mundo e a experiência - Menezes, Lis Angelis Padilha de (2011)
This work aims at investigating the convergent articulation between three philosophical schools phenomenology, existentialism and marxism, through the eye of Joel Martins, learning how he dealt with such issue and, mainly, pointing out the solutions encountered by himself. At that opportunity, Joel s philosophical thought became the object of study which demands the objective of answering the following query: Is it possible to establish a convergence between marxism and phenomenology according to Joel Martins affirmation? The hypothesis of this research considers that, before the singularity between phenomenology and marxism, a convergence is possible, with respect to its philosophical roots. This study collected data from bibliographical research and statements given. Three Brazilian educators, who lived with Joel Martins, gave their statements regarding the mentioned query. Joel s life is presented through a contextualized study of his childhood and youth, educational background and professional career, contributions to the post-graduation programs in Brazil, honors and acknowledgements received by him, mains works and testimonial statements from people who lived with him. Through this indirect closure to Joel s thought, there are present in this work three detailed statements from three educators: Prof. Dr. Antônio Joaquim Severino, Prof. Dr. Dermeval Saviani and Prof. Dr. Paolo Nosella, all of them contextualized and formalized the investigated problem. Based on Joel Martins texts, it is investigated the way he sees phenomenology, existentialism, marxism, education, qualitative research and the phenomenological method. This way, it is possible to highlight the analysis of my research s hypothesis. In other words, the fact that Joel did not possess a squared theoretical code ready and completed to analyze man and Brazilian education. Phenomenology, together with contributions from other schools of thoughts, including marxism, makes it possible for Joel as a very rich element for this analysis.